(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2021)
This study aimed at investigating the impact of using numbered heads strategy in developing thinking skills among sixth graders in Damascus governorate through teaching them unit two from the science textbook which is based on the steps of this strategy. The skills are restricted to six skills of the scientific thinking skills (observing, Deducting, interpreting data, classifying , measuring, and predicting). To achieve the purposes of this study, the researcher used the experimental study. The study was applied on a sample consisted of (73) students distributed in two groups, experimental and controlled groups. The researcher designed a test for thinking skills and also some lessons from Unit Two are designed. The findings of this study showed that: • There was a statistically significant difference between the mean scores of the experimental group students and the mean scores of the control group students in favor of the experimental group in the six scientific thinking skills, and in the overall thinking skills. • There was a statistically significant difference between the mean scores of the experimental group in the application of pre and direct post - tests in favor of the post application in the six scientific thinking skills, and in the overall thinking skills. - The most important research proposals: - Training teachers to use cooperative learning strategies, including the numbered heads strategy. - Paying attention to the development of scientific thinking skills of students. - Conducting studies to know the impact of the strategy of numbered heads on other educational stages.